2015
DOI: 10.1016/j.matbio.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of gelatinases in pathological and physiological processes involving the dystrophin–glycoprotein complex

Abstract: Dystrophin is a cytosolic protein belonging to a membrane-spanning glycoprotein complex, called dystrophin-glycoprotein complex (DGC) that is expressed in many tissues, especially in skeletal muscle and in the nervous system. The DGC connects the cytoskeleton to the extracellular matrix and, although none of the proteins of the DGC displays kinase or phosphatase activity, it is involved in many signal transduction pathways. Mutations in some components of the DGC are linked to many forms of inherited muscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…Since breakdown of basement membranes is also one of the hallmark events in MEB disease(11) or -dystroglycanopathy in general, elevated levels of MMPs could increase ECM protein degradation and impede cell-ECM interactions further deteriorating the clinical outcome of these patients. A similar role has been suggested for MMP2 and MMP9 in physiological and pathological conditions involving members of the dystrophin glycoprotein complex(52).…”
supporting
confidence: 65%
“…Since breakdown of basement membranes is also one of the hallmark events in MEB disease(11) or -dystroglycanopathy in general, elevated levels of MMPs could increase ECM protein degradation and impede cell-ECM interactions further deteriorating the clinical outcome of these patients. A similar role has been suggested for MMP2 and MMP9 in physiological and pathological conditions involving members of the dystrophin glycoprotein complex(52).…”
supporting
confidence: 65%
“…Membrane MMPs also control the activation of other members of the MMP family (Bellayr et al, 2009;Bozzi et al, 2015;Snyman and Niesler, 2015). Membrane MMPs also control the activation of other members of the MMP family (Bellayr et al, 2009;Bozzi et al, 2015;Snyman and Niesler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stromelysins, that is, MMP-3 or MMP-10, degrade laminin, fibronectin, elastin, and the core protein of proteoglycans present in ECM surrounding muscle fibers. Membrane MMPs also control the activation of other members of the MMP family (Bellayr et al, 2009;Bozzi et al, 2015;Snyman and Niesler, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrated MMP-10 levels to be an independent predictor of the necessity of RRT and thus put forth the use of MMP-10 as a promising marker in further studies in patients with AKI. 26 Ma et al 27 showed the importance of inflammation in cardiac ageing and the role of MMP-9 in the direct and indirect polarization of the macrophages. Also, MMP-10 levels were significantly higher in patients undergoing haemodialysis than in patients in the predialysis group and were found to be a risk factor independent of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…25 It also plays an important role in the degradation of extracellular matrix, activation of IL-1b, and division of some chemokines. 26 Ma et al 27 showed the importance of inflammation in cardiac ageing and the role of MMP-9 in the direct and indirect polarization of the macrophages. Bahrehmond et al 28 found a correlation between MMP-9 and systemic inflammatory markers and oxidative stress in patients with systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%